Development of a Recycled Materials Lab Kit for an Electrostatics Experiment - Yosep Sunandar; Neng Maryamah Maharani; Rifa'atul Maulidah (Berkala Ilmiah Pendidikan Fisika, 2024)
Lab kits play an essential role in supporting the learning process. This study aims to develop a feasible and practical physics experiment kit on static electricity from simple tools and materials. The static electricity lab kit was developed using the 4D model (define, design, develop, disseminate). The stages carried out in this study are only up to the third stage, namely development, because the output is in the form of lab kit products. The lab kit is made using simple tools and materials easily found in everyday life. The props can also be disassembled easily. Four physics teachers from different schools conducted validation of the lab kit. The validation results show that in terms of media, the lab kit has valid criteria, with a percentage of 98.08%. Regarding material, the lab kit also has valid criteria, with a percentage of 96%. Overall, the static electricity lab kit met valid criteria with an average percentage of 97.5%, showing that the lab kit could be disseminated directly to students. It is hoped that using this lab kit can help teachers explain the concept of static electricity and make it easier for students to understand it.